Post-Tradisionalisme: Membincang Basis Epistemologi dan Transformasi Gerakan Moderasi Beragama Nahdlatul Ulama - Muhamad Bindaniji; Moh Ashif Fuadi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
Islamic post-traditionalism is one of the discourses of Islamic thought that is developing in Indonesia. It emerged from the historical development of Islamic thought in Indonesia that continues to grow to find a  compatible and comprehensive format of Islam that is relevant to the problem faced by the Muslim Community. This study aims to explain the development of post-traditionalism discourse and its epistemology and the transformation of the religious moderation movement among the Nahdhatul Ulama organization. This study uses a literature study consisting of books, articles, and other relevant sources. Through a sociological-historical approach, this study concludes that post-traditionalism within Nahdlatul Ulama (NU) is not a modernist group seen from its movement and characteristics of its thoughts because they still adhere to salaf traditions. In addition, through cultural movements, Nahdlatul Ulama plays a very important role in internalizing wasathiyah through the acceptance of madzhab, Asy'ariyah creed, integration of Islam into nationality, and interfaith dialogue movements.